2015
DOI: 10.1590/s0102-865020150040000002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-inflammatory and analgesic effects of green tea (Camellia sinensis) in mice

Abstract: PURPOSE:To evaluate the anti-inflammatory and analgesic effects of green tea (Camellia sinensis) in mice. METHODS:The anti-inflammatory effect of alcoholic extracts of green tea (AE) was evaluated in a cell migration assay with four groups of six Swiss mice receiving 0.07g/Kg or 0.14g/Kg EA (treatment groups), saline (negative control) or 10mg/Kg indomethacin (positive control) by gavage. One hour later 300 µg carrageen an was administered intraperitoneally or subcutaneously. The analgesic effect was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…Syarayah reports that EGCG as an antioxidant works by lowering the phosphorylation of IkB to block the IL-1β that is induced by the activation of NF-kB. Mota reports that 140 mg/kg of EGCG shows a decrease of the expansion of cell inflammation in the mice that have been induced with inflammation [18]. …”
Section: -4mentioning
confidence: 99%
“…Syarayah reports that EGCG as an antioxidant works by lowering the phosphorylation of IkB to block the IL-1β that is induced by the activation of NF-kB. Mota reports that 140 mg/kg of EGCG shows a decrease of the expansion of cell inflammation in the mice that have been induced with inflammation [18]. …”
Section: -4mentioning
confidence: 99%
“…They are comprised on epigallocatechin gallate (23.4-112.4 lg/ml) as the major component, followed by epigallocatechin (18.4-78.9 lg/ml), epicatechin gallate (5.6-29.6 lg/ml), epicatechin (4.6-14.5 lg/ml) and catechin (3.2-8.2 lg/ml) [11]. The catechins effectively scavenge oxy-radicals involved in the pathogenesis of many chronic diseases, including cardiovascular diseases, cancer, neurodegenerative diseases, and ageing [12], antioxidant and prebiotic activities [13], anticancer [8], antidiabetic [14], antiinflammatory and analgesic effect [15].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are a group of secondary metabolites widely found in different plant organs such as fruits and leaves and their related processing products. Many studies have demonstrated that daily consumption of polyphenols-rich beverages and food such as green tea and olive oil is associated with a low incidence of several diseases including cancer, diabetes, obesity, leukemia, Parkinson's and cardiovascular diseases (Visioli et al, 2002;Mota et al, 2015). The beneficial health properties of green tea and olive oil consumption are related mainly to EGCG and HTyr, respectively, two phenolic compounds characterized by a wide range of biological activities (Visioli et al, 2002;Mota et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that daily consumption of polyphenols-rich beverages and food such as green tea and olive oil is associated with a low incidence of several diseases including cancer, diabetes, obesity, leukemia, Parkinson's and cardiovascular diseases (Visioli et al, 2002;Mota et al, 2015). The beneficial health properties of green tea and olive oil consumption are related mainly to EGCG and HTyr, respectively, two phenolic compounds characterized by a wide range of biological activities (Visioli et al, 2002;Mota et al, 2015). (-)-Epigallocatechin-3-gallate is the most abundant catechin phenolic compound found in Camellia sinensis L. leaves; and it is chemically characterized by the presence of two pyrogallol moieties ( Figure S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation